MAKNA PENDERITAAN KRISTUS DALAM 1 PETRUS 2:18-21 - Made Nopen Supriadi; Iman Kristina Halawa (Sekolah Tinggi Teologi Arastamar Bengkulu, 2018)
Suffering is a part of human life after falling into sin. Jesus Christ gave the principle of life carrying the cross. Therefore believers are not free from suffering. Because suffering cannot be avoided, suffering must be faced by believers. Therefore it is very important to provide insight into suffering in 1 Peter. Therefore through this article can open the understanding of believers to face suffering.